2003
DOI: 10.1242/dev.00577
|View full text |Cite
|
Sign up to set email alerts
|

Modes of intercellular transcription factor movement in theArabidopsisapex

Abstract: A recent and intriguing discovery in plant biology has been that some transcription factors can move between cells. In Arabidopsis thaliana, the floral identity protein LEAFY has strong non-autonomous effects when expressed in the epidermis, mediated by its movement into underlying tissue layers. By contrast, a structurally unrelated floral identity protein, APETALA1, has only limited non-autonomous effects. Using GFP fusions to monitor protein movement in the shoot apical meristem and in floral primordia of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(174 citation statements)
references
References 50 publications
9
161
0
4
Order By: Relevance
“…However, other NCATFs, like LFY have been suggested to move cell to cell via a diffusionbased non-selective mode in which the NCATF does not need a direct interaction with PD components (Wu et al, 2003). In this regard, mCherry is an example of non-selective/diffusionbased movement.…”
Section: Genome-wide Screening For Non-cell-autonomous Transcription mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other NCATFs, like LFY have been suggested to move cell to cell via a diffusionbased non-selective mode in which the NCATF does not need a direct interaction with PD components (Wu et al, 2003). In this regard, mCherry is an example of non-selective/diffusionbased movement.…”
Section: Genome-wide Screening For Non-cell-autonomous Transcription mentioning
confidence: 99%
“…Other well-characterized NCATFs include the floral homeotic proteins, LEAFY (Sessions et al, 2000;Wu et al, 2003), AGAM-OUS (Urbanus et al, 2010), DEFICIENS and GLOBOSA (Perbal et al, 1996), as well as TFs involved in root development, such as the Arabidopsis GRAS family member, SHORT ROOT (SHR) (Nakajima et al, 2001), CAPRICE (CPC), a Myb-like DNA-binding domain protein (Kurata et al, 2005;Wada et al, 2002), basic helix-loop-helix proteins GLABRA 3 (GL3) and ENHANCED GLABRA 3 (EGL3) (Bernhardt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Because the interactions between DOT/UFO and ALF/LFY and the target promoters are direct, cell nonautonomy probably results from the intercellular movement of DOT/ UFO rather than that of a downstream factor. Given that DOT is not fully targeted to an intracellular compartment, it is likely to move between cells by passive diffusion, similar to LFY (Sessions et al, 2000;Wu et al, 2003), which would result in a DOT gradient within the flower (Figure 8). Weak fim and dot alleles primarily affect petal development (Ingram et al, 1997) (Figure 1), suggesting that the activation of B genes requires higher DOT and FIM activity than the activation of C genes.…”
Section: Role Of Ufo and Dot In Flower Developmentmentioning
confidence: 99%
“…Because this effect of DOT requires ALF ( Figure 6A), it appears that ALF expression in the apical FM can alter the identity of the lateral IM in a non-cellautonomous manner. It was previously shown that the cell nonautonomy of LFY activity is associated with the movement of the protein between meristem cells (Sessions et al, 2000;Wu et al, 2003). Thus, it is the transcription pattern of DOT in the apex, rather than that of ALF, that restricts floral identity to the apical meristem and specifies the cymose architecture.…”
Section: Evolution and Development Of Distinct Inflorescencesmentioning
confidence: 99%
“…Wu et al (2003) suggested that cell-to-cell movement of transcription factors results from free diffusion in a non-targeted fashion (Wu et al, 2003). On the other hand, Sessions et al (2000) showed that two independent transcription factors can traffic long and short ranges in a targeted fashion.…”
Section: Discussionmentioning
confidence: 99%